Defining Identity Crimes - Jamieson, Rodger (2008)
The objective of this paper is to report on the definitions of the terms used and in use across different regions for identity crime, namely, identity fraud, identity theft, and identity deception. The purpose is to clarify the meaning of the terms used with a view to gaining a consensus amongst the various stakeholders. This consensus is essential to enable further research. Without consensus measurement and comparisons are meaningless. Our study of identity fraud has an industry-driven research agenda. A grounded theory research methodology is used when interviewing government agencies and private organisation participants. Interviews sought to better understand current information and communications technology (ICT) practitioners’ security and privacy issues with respect to identity fraud perpetrator attacks. We found there to be consensus among stakeholders for the meaning of identity fraud and identity theft but less agreement for identity deception